Antidyskinetic effect of A2A and 5HT1A/1B receptor ligands in two animal models of Parkinson's disease. Issue 4 (12th February 2016) - Pinna, Annalisa; Ko, Wai Kin D.; Costa, Giulia; Tronci, Elisabetta; Fidalgo, Camino; Simola, Nicola; Li, Qin; Tabrizi, Mojgan Aghazadeh; Bezard, Erwan; Carta, Manolo; Morelli, Micaela
Abstract: Background: The serotonin 5‐HT1A/1B receptor agonist eltoprazine suppressed dyskinetic‐like behavior in animal models of Parkinson's disease (PD) but simultaneously reduced levodopa (l ‐dopa)–induced motility. Moreover, adenosine A2A receptor antagonists, such as preladenant, significantly increasedl ‐dopa efficacy in PD without exacerbating dyskinetic‐like behavior. Objectives: We evaluated whether a combination of eltoprazine and preladenant may prevent or suppressl ‐dopa–induced dyskinesia, without impairingl ‐dopa's efficacy in relieving motor signs, in 2 PD models: unilateral 6‐hydroxydopamine–lesioned rats and 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP)–treated monkeys. Methods: Rotational behavior and abnormal involuntary movements, or disability andl ‐dopa–induced dyskinesia were evaluated in 6‐hydroxydopamine–lesioned rats and MPTP‐treated monkeys, respectively. Moreover, in the rodent striatum, induction of immediate–early gene zif‐268, an index of long‐term changes, was correlated with dyskinesia. Results: In 6‐hydroxydopamine–lesioned rats, combined administration ofl ‐dopa (4 mg/kg) plus eltoprazine (0.6 mg/kg) plus preladenant (0.3 mg/kg) significantly prevented or reduced dyskinetic‐like behavior without impairing motor activity. Z if‐268 was increased in the striatum of rats treated withl ‐dopa andl ‐dopa plus preladenant compared with vehicle. In contrast, rats treated with eltoprazine (with or without preladenant) had lower zif‐268 activation after chronic treatment in both the dyskinetic andl ‐dopa–non‐primed groups. Moreover, acutel ‐dopa plus eltoprazine plus preladenant prevented worsening of motor performance (adjusting step) and sensorimotor integration deficit. Similar results were obtained in MPTP‐treated monkeys, where a combination of preladenant with eltoprazine was found to counteract dyskinesia and maintain the full therapeutic effects of a low dose ofl ‐dopa. Conclusions: Our results suggest a promising nondopaminergic pharmacological strategy for the treatment of dyskinesia in PD. © 2016 International Parkinson and Movement Disorder Society